2017
DOI: 10.1515/enr-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Eff ects of hemin, a heme oxygenase-1 inducer in L-arginine-induced acute pancreatitis and associated lung injury in adult male albino rats

Abstract: Objective. Th e aim of the current study was to assess the protective outcome of hemin, a heme oxygenase-1 (HO-1) inducer on L-arginine-induced acute pancreatitis in rats. Acute pancreatitis (AP) is considered to be a critical infl ammatory disorder with a major impact on the patient health. Various theories have been recommended regarding the pathophysiology of AP and associated pulmonary complications.Methods. Twenty-four adult male albino rats were randomly divided into four groups: control group, acute pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
5
18
0
Order By: Relevance
“…The results of the present study demonstrated that administration of L-arginine to rats produced severe AP, which was confirmed with histopathological examination. In addition, marked increase in the serum levels of pancreatic enzymes, NO, CORT and TNF-α, and pancreatic MDA and iNOS levels were detected what is in a line with previous studies (Ucmak et al 2016;Yilmaz et al 2016;Aziz et al 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present study demonstrated that administration of L-arginine to rats produced severe AP, which was confirmed with histopathological examination. In addition, marked increase in the serum levels of pancreatic enzymes, NO, CORT and TNF-α, and pancreatic MDA and iNOS levels were detected what is in a line with previous studies (Ucmak et al 2016;Yilmaz et al 2016;Aziz et al 2017).…”
Section: Discussionsupporting
confidence: 91%
“…An elevated level of NO could be ascribed to induction of iNOS that was evoked by inflammatory cytokines. NO reacts with superoxide anion to form peroxynitrite that can react directly with lipid, protein and DNA resulting in cellular dysfunction and tissue injury what has been demonstrated in many studies (Biradar and Veeresh 2013;Al-Malki 2015;Hasan et al 2015;Aziz et al 2017).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…HMGB1 could activate toll-like receptors 4 (TLR4) signaling pathway, which is indispensable for the inflammatory process, and the specific inhibitors of HMGB1 or TLR4 (such as eritoran and [(S,R)-3-phenyl-4,5-dihydro-5-isoxasole acetic acid)] could alleviate the inflammation and improve the prognosis (33)(34)(35). The present study revealed that TNF-α and HMGB1 were upregulated in the SAP and SAP + BDG groups compared with the control groups, but BDG decreased the levels of TNF-α significantly and HMGB1 at 6 h. HO-1 is considered as an important anti-inflammatory factor, which is responsible for cytothesis and tissue protection (36). HO-1 could exert anti-inflammatory effects via the production of carbon monoxide (CO), which may be a possible factor of early treatment of SAP, while CO has been proven effective in some immuno-inflammatory and autoimmune diseases (37,38).…”
Section: Discussionmentioning
confidence: 54%
“…This is in accordance with El-Rahman et al (2011) [21] and Hasan et al (2015) [22] . L-arginine produces biochemical and histological changes like that of human AP [23] . It distorts the membranes of zymogen granules and release their enzymes to the interstitium causing inflammation [22] .…”
Section: Discussionmentioning
confidence: 92%